Interspecies cross-feeding orchestrates carbon degradation in the rumen ecosystem. (November 2018) - Solden, Lindsey; Naas, Adrian; Roux, Simon; Daly, Rebecca; Collins, William; Nicora, Carrie; Purvine, Sam; Hoyt, David; Schückel, Julia; Jørgensen, Bodil; Willats, William; Spalinger, Donald; et al.
Abstract Because of their agricultural value, there is a great body of research dedicated to understanding the microorganisms responsible for rumen carbon degradation. However, we lack a holistic view of the microbial food web responsible for carbon processing in this ecosystem. Here, we sampled rumen-fistulated moose, allowing access to rumen microbial communities actively degrading woody plant biomass in real time. We resolved 1, 193 viral contigs and 77 unique, near-complete microbial metagenome-assembled genomes, many of which lacked previous metabolic insights. Plant-derived metabolites were measured with NMR and carbohydrate microarrays to quantify the carbon nutrient landscape. Network analyses directly linked measured metabolites to expressed proteins from these unique metagenome-assembled genomes, revealing a genome-resolved three-tiered carbohydrate-fuelled trophic system. This provided a glimpse into microbial specialization into functional guilds defined by specific metabolites. To validate our proteomic inferences, the catalytic activity of a polysaccharide utilization locus from a highly connected metabolic hub genome was confirmed using heterologous gene expression. Viral detected proteins and linkages to microbial hosts demonstrated that phage are active controllers of rumen ecosystem function. Our findings elucidate the microbial and viral members, as well as their metabolic interdependencies, that support in situ carbon degradation in the rumen ecosystem. A combination of proteomics, metagenome-assembled genomes and heterologous gene expression experiments reveals a trophic system for carbon utilization in the moose rumen microbiome and provides insights into phage dynamics in this ecosystem.